Guidelines for increasing the number of customers for BAAC Perm Rak 12/10 and BAAC Taweerak 99 case studies, Chanthaburi Province - Thongkam, Onuma (Journal for Developing the Social and Community, 2022)
Objectives of this article were to study the opinions about the decision-making process for saving money and formulate guidelines for increasing customer numbers of the BAAC Life Assistance, Permrak and BAAC Taweerak 99; case studies Chanthaburi Province. The study was compiled from questionnaires and interviews. The population and sample were interviewed by the 10 people of BAAC executive staff in Chanthaburi Province, and 400 customers who visited at The BAAC branch in Chanthaburi province answered a questionnaire. The overall mean of marketing mix factors product, staff and service processes is at the highest level. Therefore, proposing a strategy with a focus on products in which the center will focus on upgrading and developing better products. Service process should reduce work processes, HR need to enhance employee’s knowledge, increase work efficiency. It should also increase a variety of marketing communication pattern by focus on online communication, adding more promotional activities. Offers create a linked to the A-Reward points system. It is one of the channels for the bank's CRM via Line system to encourage all target customers to purchase products and continue to use the life support deposit service. And come back to use the service repeatedly including Inviting people in the family or acquaintances to use the bank's services